2012
DOI: 10.1002/adma.201104182
|View full text |Cite
|
Sign up to set email alerts
|

Lasing from Epitaxially Oriented Needle Crystals of a Thiophene/Phenylene Co‐Oligomer

Abstract: Optically pumped lasing of epitaxially oriented molecular crystals is presented. Needle-like crystals of a thiophene/phenylene co-oligomer is grown along the [110] direction of a KCl substrate. The fluorescence light is one-dimensionally confined and amplified by the self-waveguiding effect in the elongated needles. The Fabry-Pérot resonation by the terminated ends results in laser oscillations corresponding to the needle length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…These observations mean that the BP2T-OMe and BP2T crystals are potentially useful for laser media. 27,35) The present studies are expected to provide important information for the design of organic lasers.…”
Section: Discussionmentioning
confidence: 94%
“…These observations mean that the BP2T-OMe and BP2T crystals are potentially useful for laser media. 27,35) The present studies are expected to provide important information for the design of organic lasers.…”
Section: Discussionmentioning
confidence: 94%
“…needle-like crystals by epitaxial growth. 8 Moreover, spectrally narrowed emission has been reported for a lightemitting field-effect transistor (FET) with a single-crystal TPCO under AC-gate operation, 9 demonstrating a potentials of TPCOs for electrically pumped lasing.…”
Section: Introductionmentioning
confidence: 99%
“…12 Yanagi et al have reported TPCO epitaxially crystallized in oriented needles grown on cleaved (001) surfaces of potassium chloride (KCl) single crystals using the hot-wall epitaxy method. [13][14][15] Noteworthy optical properties such as a selfwaveguided feature, stimulated resonance Raman scattering, 16 and lasing 17 have been observed in the needles. The lasing of TPCO crystals has been demonstrated in microdisk structures, occurring in whispering gallery modes (WGMs).…”
mentioning
confidence: 99%